Verifying Different-Modality Properties for Concepts Produces Switching Costs - Pecher, Diane; Zeelenberg, René; Barsalou, Lawrence W. (Psychological Science, 2003)
According to perceptual symbol systems, sensorimotor simulations underlie the representation of concepts. It follows that sensorimotor phenomena should arise in conceptual processing. Previous studies have shown that switching from one modality to another during perceptual processing incurs a processing cost. If perceptual simulation underlies conceptual processing, then verifying the properties of concepts should exhibit a switching cost as well. For example, verifying a property in the auditory modality (e.g., BLENDER-loud) should be slower after verifying a property in a different modality (e.g., CRANBERRIES-tart) than after verifying a property in the same modality (e.g., LEAVES-rustling). Only words were presented to subjects, and there were no instructions to use imagery. Nevertheless, switching modalities incurred a cost, analogous to the cost of switching modalities in perception. A second experiment showed that this effect was not due to associative priming between properties in the same modality. These results support the hypothesis that perceptual simulation underlies conceptual processing.